Edible Bird's Nest treatment effects on subchondral bone and articular cartilage changes and synovial fluid proteome profiles in an osteoarthritis rabbit model - Syed Sulaiman, Sharifah Zakiah (2022)
Osteoarthritis (OA) is characterised by progressive degeneration of articular cartilage, subchondral bone changes and synovium inflammation. Animal models are important and can demonstrate different features depending on method of induction which can resemble primary and secondary OA in humans. The choice of animal models used is based on the type and duration of research and outcome measurements. Currently, the goals for OA treatment mainly focus to alleviate disease signs and symptoms. Numerous natural products including Edible Bird’s Nest (EBN) have been studied extensively in order to create potential therapies for inflammatory disorders such as arthritis. Previous studies have reported the antioxidative, anti-inflammatory and bone-strengthening effects of EBN. This study is divided into two parts. The first study is aimed to compare subchondral bone and articular cartilage changes and proteome profiles for surgically induced and chemically induced rabbit model of osteoarthritis at different time points. Based on the first study, more suitable model is chosen for the second study which is aimed to observe the effects of EBN in ameliorating OA development at different time points. For the first part of the study, New Zealand white rabbits underwent either anterior cruciate ligament transection (ACLT) procedure or injected intra-articularly with monosodium iodoacetate (MIA, 8 mg) into the right knee and were further divided into week 4 (n=5), week 8 (n=5) and week 12 (n=5) groups. The joints were subjected to micro-computed tomographic (micro-CT) analysis and histological evaluation. The synovial fluid were subjected to MALDI TOF/TOF analysis. Bone volume over tissue volume for surgically induced group increased in femur (35.35%) and tibia (32.82%) during week 12 which suggested bone remodelling whereas chemically induced group showed persistent bone resorption with decreased value of BV/TV in femur (27.12%) and tibia (26.82%). For histopathological grading of articular cartilage in femur and tibia, surgically induced group showed minimal changes during week 12 with median values of 1 and 2 in femur and tibia, respectively. As for chemically induced group, more severe changes were recorded with median values of 4.5 and 5 with significant difference with control group (p=0.0184, 0.0208) in femur and tibia, respectively. Micro-CT and histopathological analysis revealed that subchondral bone remodelling precede articular cartilage damage in surgically induced group, and vice versa in chemically induced group. Proteome profiles showed peak OA progression during week 12 for surgically induced group with upregulation of gelsolin and serotransferrin protein which involved in advanced OA. For chemically induced group, OA progression is the highest during early stage indicated by high upregulation of apolipoprotein I-IV precursor and serpin peptidase inhibitor protein during week 4 but were later downregulated. The results showed different pathogenic mechanisms for both induction method. For the second part of the study, New Zealand white rabbits were chemically induced (MIA, 8 mg) and divided into four groups; (1) negative control (n=9): non-treated osteoarthritis, (2) positive control (n=15): OA + diclofenac sodium 2 mg/kg daily orally, (3) low dosage (n=15): OA + 75 mg/kg hydrolysed EBN, (4) high dosage (n=15): OA + 150 mg/kg hydrolysed EBN. The joints were subjected to micro-CT analysis and histological evaluation and the synovial fluid subjected to LCMS/MS analysis. Micro-CT analysis showed a 22% increase in BV/TV value and 10% decrease in total porosity (PO) in treatment group that showed bone integrity improvement. Histopathological results revealed comparable changes between positive control group and EBN treatment group. There was upregulation of annexin-1, a protein involved in resolution of inflammation and downregulation carbonic anhydrase II, a protein associated with bone resorption process. Overall, morphology evaluation showed that EBN supplementation can inhibit osteoclastic activity but have no effect on cartilage damage. Protein expression showed action of several proteins involved in bone resorption inhibition and resolution of inflammation via several signalling pathways which includes toll-like receptor (TLR) and NF-κB signalling pathways.